TINJAUAN YURIDIS PUTUSAN BEBAS DALAM TINDAK PIDANA PEMALSUAN AKTA KELAHIRAN YANG DIGUNAKAN SEBAGAI DASAR MELAKUKAN JUAL BELI TANAH (Studi Putusan Mahkamah Agung RI No. 387 K/Pid/2021) - Nabila, Sarah (Jurnal Perspektif Hukum, 2023)
The product produced in the judicial process, especially criminal justice, is a judge's decision. The judge based on the norms used to analyze the laws and regulations related to the issuance of an acquittal (vrijspraak) against the defendant for the crime of forging a birth certificate. The problem that arises is the regulation of criminal law for the perpetrators of the crime of falsifying birth certificates in buying and selling land? The form of criminal responsibility for the act and what is the basis for the consideration of the judge who tried the defendant for Decision No. 387 K/Pid/2021 Raba Bima District Court? The research method used is secondary data consisting of applicable laws and regulations, books, journals and other supporting data relevant to the research title. The judge decided with an acquittal in the crime of falsifying a birth certificate which was used as the basis for buying and selling land in the decision on Case Number 387 K/Pid/2021 against the defendant based on the consideration that the panel of judges considered that the defendant had not found any unlawful act and without rights (which must be judged by intention/intent/knowledge of the unlawful nature of an act in an actor).